Análisis de la oferta estadística vinculada a la economía popular y solidaria del Ecuador, período 2021-2022. - Barco Véliz, Diana Carolina (2022)
In this article, an analysis was carried out on the existence or not of statistical operations and administrative records with statistical potential that are linked to the popular and solidarity economy, for which the statistical offer of Ecuador for the period 2021-2022 is studied, including the experiences of other countries. The main instrument is the national statistical programs and the inventory of statistical operations and records managed by the statistical institutes of each country analyzed, complemented by the use of comparative matrices for the characterization and identification of each statistical operation and administrative records with potential statistical. Then, with the results obtained, an analytical reflection was generated on the theoretical approach with which the popular and solidarity economy is currently measured in Ecuador, contrasting with the progress that other countries have on the generation of statistics for this sector.